DETERMINING THE EFFECTIVENESS OF BUSINESS PROCESSES OF BUILDING COMPANIES TAKING INTO CONSIDERATION THE PRINCIPLES OF SUSTAINABLE DEVELOPMENT THE OPERATORS OF ACTIVITIES - Глух, Вадим (SWorldJournal, 2025)
The article discusses the methodological foundations for assessing management quality from the perspective of business process management in construction companies, to include key principles to consider in sustainable development. The purpose of the arti